The effectiveness of exercise on the symptoms in breast cancer patients undergoing adjuvant treatment: an umbrella review of systematic reviews and meta-analyses - Yuan Zhao; Leiwen Tang; Jing Shao; Dandan Chen; Yueying Jiang; Panpan Tang; Xueqing Wang (Frontiers in Oncology, 2023)
BackgroundExercise has the potential to reduce symptoms for breast cancer patients during adjuvant treatment, and high-quality systematic reviews are essential for guiding clinical practice. The objective of this umbrella review is to examine current research evidence concerning the effectiveness of exercise on symptom management in breast cancer patients undergoing adjuvant treatment.MethodsAn umbrella review was conducted. We searched for eligible systematic reviews through 11 databases until August 13rd, 2023. Two authors independently screened titles and abstracts, assessing the full-text studies based on inclusion criteria. We used AMSTAR-2 to appraise the quality of the meta-analyses. The results would be presented with narrative summaries if the replication rate of the original study for a symptom was higher than 5% (calculated via the Corrected Covered Area, CCA). The protocol was documented in the PROSPERO registry (CRD42023403990).ResultsOf the 807 systematic reviews identified, 15 met the inclusion criteria, and 7 symptoms were the main focus. The main form of exercise mentioned was aerobic combined resistance exercise. The results of the quality assessment were mostly critically low (10/15). The repetition rate calculated by CCA showed moderate to very high repetition rates (10% to 18.6%). The findings of the included reviews indicated that the effects of exercise on relieving symptoms during breast cancer adjuvant treatment were mixed.ConclusionsResearch is still needed to confirm the majority of studies’ recommendations for exercise during adjuvant treatment for breast cancer patients, as it is crucial for managing symptoms in the rehabilitation process. To increase the efficiency of exercise in symptom management, future studies may focus more on the application of bridge symptoms, symptom networks, and ecological instantaneous assessment.